2006
DOI: 10.1158/1055-9965.epi-06-0352
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Prevention of Squamous Cell Carcinoma of the Skin by Regular Sunscreen Use

Abstract: Half of all cancers in the United States are skin cancers. We have previously shown in a 4.5-year randomized controlled trial in an Australian community that squamous cell carcinomas (SCC) but not basal cell carcinomas (BCC) can be prevented by regular sunscreen application to the head, neck, hands, and forearms. Since cessation of the trial, we have followed participants for a further 8 years to evaluate possible latency of preventive effect on BCCs and SCCs. After prolonged follow-up, BCC tumor rates tended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
221
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(232 citation statements)
references
References 14 publications
4
221
0
7
Order By: Relevance
“…Broadspectrum chemical and physical sunscreens have been shown to reduce ultraviolet light exposure per unit time when properly applied. 121,122 Routine use of sunscreens is recommended in combination with other sun-protective behaviors such as seeking shade and wearing broad-brimmed head coverings.…”
Section: Follow-up and Reducing Risk For Future Skin Cancersmentioning
confidence: 99%
“…Broadspectrum chemical and physical sunscreens have been shown to reduce ultraviolet light exposure per unit time when properly applied. 121,122 Routine use of sunscreens is recommended in combination with other sun-protective behaviors such as seeking shade and wearing broad-brimmed head coverings.…”
Section: Follow-up and Reducing Risk For Future Skin Cancersmentioning
confidence: 99%
“…Various measures can be taken to prevent skin cancer, some of which include avoiding exposure to solar radiation at times of highest incidence of UV radiation, mainly between 10 am and 3 pm, using accessories such as hats, sunglasses with UV protection and umbrellas, but the correct use of sunscreens with an appropriate sun protection factor (SPF) is still the most efficient way of preventing skin cancer (Klug et al, 2010;United, 2011). An Australian study has shown that the regular use of sunscreens can help in the prevention of squamous cell carcinoma (a type of skin cancer) of head, neck and forearm (Van der Pols et al, 2006). Given the importance of photoprotection and skin disease prevention, the effectiveness of sunscreens products has been the object of more and more studies.…”
Section: Skin Cancer and Sun Radiationmentioning
confidence: 99%
“…Typically, the organic UV filters are called chemical filters, as their mode of action is related to chemical changes in their molecules that prevent UV radiation reaching the skin. The inorganic UV filters are called physical, because their mode of skin protection against solar radiation is associated with physical phenomena, such as scattering and reflection of UV radiation (Antoniou et al, 2008;Jin et al, 2008;Seite et al, 2000;Van der Pols et al, 2006;Wang, Balagula, Osterwalder, 2010). However, the correct denomination of UV filters is inorganic and organic, because both of them are chemical products differing in their molecular composition and physical and chemical terms refer to the action mode of the UV filters (Morabito et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Nambour Skin Cancer Prevention Trial evaluated daily sunscreen use and beta-carotene supplementation in the prevention of BCC and SCC. The trial showed that, in comparison with people randomized to using sunscreen at their discretion, if at all, people randomized to daily use of a broad-spectrum SPF15+ sunscreen had no reduction in BCC but a 40 % reduction in SCC tumors at the conclusion of the trial [20]-a reduction maintained 8 years later [21]. Rate of acquisition of AKs was also reduced in the daily sunscreen group [22], as was the time to subsequent BCCs after the first BCC [23] in the trial period.…”
Section: Pre-2009 Skin Cancer Prevention Trials and Systematic Reviewsmentioning
confidence: 99%